2006
DOI: 10.1080/00071660600829209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal douching and different semen extenders on bacterial load and fertility in turkeys

Abstract: 1. A study on artificial insemination of Beltsville Small White turkeys investigated the effect on bacterial load and fertility of vaginal douching with diluents containing Gentamicin 400 microg/ml and different semen extenders. 2. Irrespective of the extenders used, vaginal douching with Gentamicin reduced the microbial load of the vagina with resultant improvement in fertility and hatchability and corresponding reduction in embryonic mortality. 3. Eggs from hens inseminated with semen extended with Beltsvill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…However, the BPSE extender was found to be superior to CARI and LAKE diluents in maintaining the motility, viability and normal morphology of spermatozoa under liquid storage for 48 hours at 4°C. These findings were in line with those reported in past research in Turkey and guinea fowl spermatozoa (Venkatesh 2005;Laffaldano 2010;Keerthy 2016). Furthermore, good reproductive rates (74%) were obtained in turkey sperm diluted with BPSE extender, inseminated after twenty-four (24) hours of storage (Burrows and Quinn 1937), which could also be due to preserved higher spermatozoa motility (Keerthy 2016).…”
Section: Discussionsupporting
confidence: 93%
“…However, the BPSE extender was found to be superior to CARI and LAKE diluents in maintaining the motility, viability and normal morphology of spermatozoa under liquid storage for 48 hours at 4°C. These findings were in line with those reported in past research in Turkey and guinea fowl spermatozoa (Venkatesh 2005;Laffaldano 2010;Keerthy 2016). Furthermore, good reproductive rates (74%) were obtained in turkey sperm diluted with BPSE extender, inseminated after twenty-four (24) hours of storage (Burrows and Quinn 1937), which could also be due to preserved higher spermatozoa motility (Keerthy 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Most poultry semen extenders do contain an antibiotic with gentamicin being the most common antibiotic. One study showed that using an antibiotic solution as a douche of the distal oviduct just before AI improved fertility and hatchability as well as decreased embryonic death in turkeys [Omprakash and Venkatesh, ]. The extender used in this study did include gentamicin but the female's cloacas were not flushed with antibiotic before AI.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive system of birds is unique in its anatomy [3], providing a great precondition for possible bacterial contamination of semen, which is a main factor influencing the success of artificial insemination. Specifically, semen passing through the vas deferens into the cloaca is at high risk of being infested with fecal bacteria originating from the gastrointestinal tract [2,4]. Sperm agglutination, morphological abnormalities, and DNA damage of male gametes, seminal oxidative stress, and a subsequent endangered fertility in humans, bulls, rabbits, and boars, have been often associated with bacterial infections of the urogenital tract [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%